Subacute combined degeneration induced by nitrous oxide inhalation: Two case reports. Issue 18 (May 2020) - Zhao, Bing; Zhao, Lixian; Li, Zhixing; Zhao, Renliang
Abstract: Rationale: Nitrous oxide (N2 O), commonly known as "laughing gas, " is being increasingly abused by young people as a recreational drug; this can subsequently result in myelopathy and peripheral neuropathy, however, in China, few cases of neurologic deterioration by N2 O abuse have been reported. Patient concerns: Herein, we present 2 patients who developed progressive limb weakness, numbness, and ataxia. Both of them had recreationally inhaled N2 O intermittently for a long time. Diagnosis: Subacute combined degeneration (SCD) based on myelopathy and polyneuropathy after N2 O abuse. Interventions: The 2 patients were treated with cessation of N2 O inhalation, methylcobalamin capsule 500 μg tid (ter in die, which means 3 times a day), and compound vitamin B 1 tablet tid p.o.(per os, which means taken orally) for 1 month. Outcomes: The symptoms of altered sensation and the patients' gait improved significantly. Lessons: The 2 cases raise awareness of the important mechanisms of N2 O neurotoxicity, and clinicians should be made fully aware of such substance-related diseases. The incidence of N2 O -induced neurotoxicity is insufficiently recognized and should be considered as an important cause of SCD, especially in adolescents with undifferentiated weakness and abnormal sensation; this is essential because serious complications such as irreversible paralysis can result from the absence of early diagnosis and treatment.